Measuring the cosmic ray mass composition with LOFAR - Buitink, S.; Corstanje, A.; Enriquez, J. E.; Falcke, H.; Hörandel, Jörg R.; Huege, T.; Nelles, Anna; Rachen, J. P.; Rossetto, L.; Schellart, P.; Scholten, O.; Ter Veen, S.; et al. (Proceedings of Science, 2015)
The LOFAR radio telescope measures the radio emission from air showers with unprecedented precision. In the dense core individual air showers are detected by hundreds of dipole antennas. The complicated radio pattern on the ground is accurately reproduced by modern radio simulation codes and contains information about the longitudinal shower development. With a hybrid reconstruction technique, we measure the depth of the shower maximum with an accuracy of less than 20 g/cm2. We will present the latest LOFAR results of cosmic-ray mass analysis in the energy regime of 1017 eV to 1018 eV. This range is of particular interest as it may harbor the transition from a Galactic to an extragalactic origin of cosmic rays.
CRIS-Team Scopus Importer:2023-08-15